Cyclopalladation in the Periphery of a NHC Ligand as the Crucial Step in the Synthesis of Highly Active Suzuki–Miyaura Cross‐Coupling Catalysts. Issue 58 (18th September 2017) - Fizia, Agnes; Gaffga, Maximilian; Lang, Johannes; Sun, Yu; Niedner‐Schatteburg, Gereon; Thiel, Werner R.
Abstract: Starting from 2, 4‐dichloropyrimidine, 4‐(2‐dialkylamino)pyrimidinyl functionalized mesitylimidazolium chlorides are accessible in a five‐step reaction sequence. Two routes leading to palladium NHC complexes derived from these ligands have been worked out: By transmetalation with the corresponding NHC‐AgCl complexes, C, N‐coordinated palladium(II) complexes can be obtained. Treatment of palladium dichloride with the imidazolium salts in pyridine and in the presence of K2 CO3 gives cyclometalated and thus C, C‐coordinated compounds. The reactivities of all these compounds were investigated in detail as well as their performance in the catalytic Suzuki–Miyaura cross‐coupling reaction. It turned out that the C, C‐coordinated derivatives exhibit high catalytic activities in the coupling of arylboronic acids with aryl chlorides, which is consistent with the generally accepted mechanistic ideas on substrate activation. Abstract : Coordination matters ! Two different modes of coordinating an aminopyrimidine to the palladium site of C−C coupling catalysts gives rise to very different reactivities (see figure).